Downregulation of MYCN through PI3K Inhibition in Mouse Models of Pediatric Neural Cancer - Cage, Tene Aneka; Chanthery, Yvan; Chesler, Louis; Grimmer, Matthew; Knight, Zachary; Shokat, Kevan; Weiss, William A.; Gustafson, W. Clay (Frontiers in Oncology, 2015)
The MYCN proto-oncogene is associated with poor outcome across a broad range of pediatric tumors. While amplification of MYCN drives subsets of high risk neuroblastoma and medulloblastoma, dysregulation of MYCN in medulloblastoma (in the absence of amplification) also contributes to pathogenesis. Since PI3K stabilizes MYCN, we have used inhibitors of PI3K to drive degradation. In this study, we show PI3K inhibitors by themselves induce cell cycle arrest, with modest induction of apoptosis. In screening inhibitors of PI3K against MYCN, we identified PIK-75 and its derivative, PW-12, inhibitors of both PI3K and of protein kinases, to be highly effective in destabilizing MYCN. To determine the effects of PW-12 treatment in-vivo, we analyzed a genetically engineered mouse model for MYCN-driven neuroblastoma and a model of MYCN-driven medulloblastoma. PW-12 showed significant activity in both models, inducing vascular collapse and regression of medulloblastoma with prominent apoptosis in both models. These results demonstrate that inhibitors of lipid and protein kinases can drive apoptosis in MYCN-driven cancers and support the importance of MYCN as a therapeutic target.